Taxonomy of the Hister criticus group, with description of a new species (Coleoptera: Histeridae) - Caterino, Michael S. (Zootaxa, 2004)
The Hister criticus group is created and defined to include 5 species: Hister criticus Marseul, H. laevimargo Lewis (= H. planimargo Lewis, New Synonomy), H. latimargo Schmidt, H. foveipygus Wenzel and Dybas, and H. guanacaste n. sp. These species occur in the Neotropical region, ranging from Panama north to extreme southern Arizona (USA). Hister latimargo appears to be an obligate associate of leafcutter ants (Atta spp.), while H. criticus has been collected in woodrat (Neotoma spp.) nests. Ecological associations for the other species are unknown. The existing species are redescribed, diagnostic characters (protibiae, pygidia, male and female genitalia) are illustrated, and habitus photographs of all species are presented. Lectotypes are designated for H. criticus, H. laevimargo, and H. planimargo.